Architecture+conception. (China : Jiangsu People's Publishing House, 2011)
This book presents the reader through the detailed project description, and a lot of beautiful pictures, more than 100 cases of well-known all over the world or unique buildings and their design.
Text in English and Chinese.
Keywords: Architectural design; Architecture -- Designs and plans